Aging and mental health - Segal, Daniel L.; Qualls, Sarah Honn; Smyer, Michael A. (Understanding aging, 2018)
"The third edition of Aging and Mental Health is filled with new updates and features, including the impact of the DSM-5 on diagnosis and treatment of older adults. Like its predecessors, it uses case examples to introduce readers to the field of aging and mental health. It also provides both a synopsis of basic gerontology needed for clinical work with older adults and an analysis of several facets of aging well. Aging and Mental Health, Third Edition is an ideal text for advanced undergraduate and graduate students in psychology, for service providers in psychology, psychiatry, social work, and counseling, and for clinicians who are experienced mental health service providers but who have not had much experience working specifically with older adults and their families".--Provided by Amazon.